Pembelajaran Kontekstual IPA Materi Ekosistem Siswa Kelas V Sekolah Dasar - Anggara Dwinata; Emy Yunita Rahma Pratiwi; Ratih Asmarani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This study aims to determine the effectiveness of the contextual learning model on learning outcomes of Natural Sciences material for the fifth grade elementary school students. The method used in this study is a quantitative method with the research design used is Pretest Posttest Control Group Design. The sample used in this study found 23 students consisting of 11 female students and 12 male students. Data analysis techniques used in this study include normality test, homogeneity test, and t-test. The results showed that there was a significant effect on the effectiveness of the contextual learning model in learning natural sciences on ecosystem materials. This can be shown by the value of the hypothesis test with a t-test of 5.501 > 2.015 (df; 44). On the other hand, which shows the significance value is the result obtained by 0.003 < 0.05 (5%). So it can be concluded that there are significant differences in the results of the post-test of students in the control and experimental groups.